Whose Goals Whose Aspirations Learning to Teach Underprepared Writers across the Curriculum - Fishman, Stephen (University Press of Colorado, 2002)
Ever since Horace Mann promoted state supported schooling in the 1850s, the aims of U.S. public education have been the subject of heated national debate. Whose Goals? Whose Aspirations? joins this debate by exploring clashing educational aims in a discipline-based university classroom and the consequences of these clashes for "underprepared" writers. In this close-up look at a White middle-class teacher and his ethnically diverse students, Fishman and McCarthy examine not only the role of Standard English in college writing instruction but also the underlying and highly charged issues of multiculturalism, race cognizance, and social class.